Leisure activities and attitude of institutionalized elderly people: a basis for nursing practice - Vivian Carla de Castro; Lígia Carreira (Universidade de São Paulo, 2015)
Aim: to identify the leisure activities performed in Long-Stay Institutions for the Elderly (LSIEs), registered in the city of Maringá-PR, Brazil, and to analyze the attitude of the elderly people toward leisure promoted by the institutions. METHOD: this was a descriptive and transversal study with a quantitative approach, carried out with 97 elderly people, through the establishment of the socio-demographic profile and the application of the Leisure Attitude Scale. The data was subjected to descriptive statistical analysis, association tests (chi-square or Fisher's) and Spearman's correlation. RESULTS: males, aged 80 or over, widowed, with one to eight years of study, who had a monthly income were predominant. Age group and income were significantly associated with the performance of leisure activities. The results reflected the positive attitude of the elderly people in relation to leisure activities, except in the behavioral component. CONCLUSION: the findings of this study indicate the need for further investigation into the difficulties linked to the attitude toward leisure in the behavioral component, considering aspects such as individual concepts of leisure and the health status of the elderly people.